Unidentified γ-ray emission towards the SNR Kes 41 revisited - Supán, Jorge Leonardo (2018)
Kes 41 is one of the Galactic supernova remnants (SNRs) that are proposed to be physically linked to γ-ray emission at GeV energies. The nature of the γ-ray photons has been explained, but inconclusively, as hadronic collisions of particles accelerated at the SNR blast wave with target protons in an adjacent molecular clump. We performed an analysis of Fermi-Large Area Telescope (LAT) data of about nine years to assess the origin of the γ-ray emission. To investigate this matter, we also used spectral modelling constraints from the physical properties of the interstellar medium towards the γ-ray emitting region along with a revised radio continuum spectrum of Kes 41 (α =-0.54 ± 0.10, Sνα). We demonstrate that the γ-ray fluxes in the GeV range can be explained through bremsstrahlung emission from electrons interacting with the surrounding medium. We also considered a model in which the emission is produced by pion decay after hadronic collisions, and confirm that this mechanism cannot be excluded.